Home Network Basis: Transmission Environments and Wired/Wireless Protocols - Chen, Walter Y. (Prentice Hall PTR, 2011)
This complete technical guide to home network media, protocols, and implementation is the first systematic technical guide to all leading transmission media and communication protocols for in-home networking.